Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.17955/tvr.110.1.618
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Potential Maximization: A Framework of Proactive Psychosocial Attributes and Tactics Used by Individuals Who Are Deaf

Abstract: The Alexander Graham Bell Association for the Deaf and Hard of Hearing helps families, health care providers and education professionals understand childhood hearing loss and the importance of early diagnosis and intervention. Through advocacy, education, research and financial aid, AG Bell helps to ensure that every child and adult with hearing loss has the opportunity to listen, talk and thrive in mainstream society. With chapters located in the United States and a network of international affiliates, AG Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Another aspect of Potential Maximization is that the individual's gradual understanding and mastery of disability-related psychosocial challenges leads to better social adjustment (Bibby et al, 1996;Goldberg, Higgins, Raskind, & Herman, 2003;Polat, 2003). A review of the literature further suggested that individuals who are deaf likely use the psychosocial skills expected of individuals with typical hearing in addition to specific skills to identify, circumvent, or master psychosocial deafness-related difficulties (Jacobs, 2010).…”
Section: Potential Maximizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Another aspect of Potential Maximization is that the individual's gradual understanding and mastery of disability-related psychosocial challenges leads to better social adjustment (Bibby et al, 1996;Goldberg, Higgins, Raskind, & Herman, 2003;Polat, 2003). A review of the literature further suggested that individuals who are deaf likely use the psychosocial skills expected of individuals with typical hearing in addition to specific skills to identify, circumvent, or master psychosocial deafness-related difficulties (Jacobs, 2010).…”
Section: Potential Maximizationmentioning
confidence: 99%
“…While there is much research on the difficulties facing individuals who are deaf, there is a paucity of research that has focused on how they can maximize their social and professional potential. In order to conduct such research, it is necessary to shift focus away from what individuals who are deaf cannot do toward investigating what they can do (Jacobs, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations